Effects of Advanced Training Techniques of Parachute and Weighted Vest on Sprint Performance of Sprinter - Anas Mehmood; Basit Ali; Syed Muhammad Bilal Gillani (The Sky)
This study investigated the effect of an advanced training technique involving parachutes and weighted vests on the sprint performance of sprinters. Thirty sprinters participated in both pretest and post-test measurements of their 30-meter sprint times. Descriptive statistics revealed a significant improvement in sprint times following the training intervention, with the mean sprint time decreasing from 4.6317 seconds in the pre-test to 4.4680 seconds in the post-test. A paired samples t-test confirmed the statistical significance of this improvement (t = 17.454, p = 0.000), with a mean difference of 0.16367 seconds. The standard deviation of differences (0.05136 seconds) and standard error mean (0.00938 seconds) indicated consistent improvements across participants. A very strong positive correlation (r = 0.826) between pre-test and posttest sprint times further validated the effectiveness of the training intervention. The findings suggest that the advanced training technique significantly enhances sprint performance and may be beneficial for sprinters aiming to improve their competitive edge. Future research could explore the long-term effects and broader applicability of this training method across different athletic populations.